Detecção de arbovírus circulantes na região Norte de Mato Grosso, Amazônia Meridional - Moraes, Ana Lucia Scarpin Ramos de (2022)
Arboviruses, especially of the families Flaviviridae, Togaviridae, and Peribunyaviridae, are among the main causes of disease in humans. Approximately 500 species of arboviruses have already been identified in the world, and 200 of them have been found in the Brazilian Amazon. Due to deforestation and urbanization, especially in the so-called "Amazon Arc of Deforestation", the appearance of arboviruses is a challenge for surveillance. Molecular methods are essential tools for the differential diagnosis of arboviruses, which allows the determination of prognosis and treatment of patients, as well as epidemiological studies for control and prevention purposes. The objective of this study was to detect the circulation of arboviruses by using molecular methods in the municipalities of the northern region of Mato Grosso, located south of the Amazon Arc of Deforestation. For this purpose, samples from patients with clinical suspicion of DENV, CHIKV and/or ZIKV were tested in MultiplexNested-PCR methods for the identification of 17 arboviruses belonging to the genera Flavivirus, Alphavirus,and Orthobunyavirus. A total of 150 samples were tested, of which 9 (6%) were positive for arboviruses. Among these samples, two were positive for DENV-2; six for DENV4 and one for MAYV. Five (5) patients were positive for dengue using immunochromatographic methods, four (4) patients were diagnosed with dengue based on clinico-epidemiological criteria Our detection of MAYV would have been missed if not for our more intensive RT-PCR surveillance for other arboviruses. The implementation of a surveillance program using molecular diagnostic methodologies favors early detection of arbovirus emergence in the population, preventing the onset of epidemics.